Computational and experimental method for estimating the residual life of gears based on vibration monitoring data - Ishin, Nikolay Nikolaevich; Gavrylov, Sergii; Goman, Arkadiy; Skorokhodov, Andrey; Dakalo, Juriy (Національний технічний університет "Харківський політехнічний інститут", 2021)
A computational and experimental method for estimating the residual life of gears in the inter-repair period is proposed. The method is based on the main provisions of the theory of vibration-pulse diagnostics of spur gears, developed at the OIM of the National Academy of Sciences of Belarus. The main performance criteria are the contact and bending endurance of the teeth. Accounting for changes in the value of the coefficient of internal dynamic load in the gearing during the operation of gears is carried out on the basis of vibration analysis during their vibration monitoring. The proposed method makes it possible to estimate the residual life of the gear mechanism at any stage of operation, providing the opportunity to organize the transition from planned preventive maintenance of machines to maintenance according to the actual condition.An example of estimating the residual life of a gear pair that limits the reliability of a two-row planetary gear motor-wheel of a heavy-duty dump truck is given.

Запропоновано розрахунково-експериментальний метод оцінки залишкового ресурсу зубчастих передач у міжремонтний період. Метод базується на основних положеннях теорії вібраційно-імпульсного діагностування прямозубих зубчастих передач, розробленої в ОIМ НАН Білорусі. Основними критеріями працездатності приймаються контактна і згинна витривалість зубів. Урахування зміни величини коефіцієнта внутрішнього динамічного навантаження в зачепленні у процесі експлуатації передач дійснюється на основі аналізу вібрацій при їх вібромоніторингу. Запропонований метод дозволяє оцінити залишковий ресурс зубчастого механізму на будь-якій стадії експлуатації, забезпечуючи можливість організувати перехід від планово-попереджувального обслуговування машин до обслуговування за фактичним станом. Наведено приклад оцінки залишкового ресурсу зубчастої пари, що лімітує надійність дворядного планетарного редуктора мотор-колеса великовантажного самоскида.
Розрахунково-експериментальний метод оцінки залишкового ресурсу зубчастих передач за даними вібромоніторингу
Keywords: inter-repair period; internal dynamic load in engagement; міжремонтний період; внутрішнє динамічне навантаження в зачепленні